2015
DOI: 10.1016/j.bbr.2015.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex surface area relates to behavioral inhibition in adolescents with and without heavy prenatal alcohol exposure

Abstract: Prenatal alcohol exposure is associated with behavioral disinhibition, yet the brain structure correlates of this deficit have not been determined with sufficient detail. We examined the hypothesis that the structure of the anterior cingulate cortex (ACC) relates to inhibition performance in youth with histories of heavy prenatal alcohol exposure (AE, n = 32) and non-exposed controls (CON, n = 21). Adolescents (12–17 years) underwent structural magnetic resonance imaging yielding measures of gray matter volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 69 publications
1
30
1
Order By: Relevance
“…These authors also reported reduced surface area in the right superior temporal gyrus and occipital-temporal region, as well as global surface area reductions in bilateral frontal, temporal, and right occipital cortex that were consistent with overall volumetric reductions of these areas. In a more recent study, we found that adolescents with heavy prenatal alcohol exposure had reduced surface area of the anterior cingulate cortex compared to non-exposed adolescents (Migliorini et al, 2015). Given the known reductions in cortical volume and the discrepant findings concerning cortical thickness, examining additional morphological features will lead to a greater understanding of structural brain alterations in individuals with heavy prenatal alcohol exposure.…”
Section: Introductionmentioning
confidence: 74%
“…These authors also reported reduced surface area in the right superior temporal gyrus and occipital-temporal region, as well as global surface area reductions in bilateral frontal, temporal, and right occipital cortex that were consistent with overall volumetric reductions of these areas. In a more recent study, we found that adolescents with heavy prenatal alcohol exposure had reduced surface area of the anterior cingulate cortex compared to non-exposed adolescents (Migliorini et al, 2015). Given the known reductions in cortical volume and the discrepant findings concerning cortical thickness, examining additional morphological features will lead to a greater understanding of structural brain alterations in individuals with heavy prenatal alcohol exposure.…”
Section: Introductionmentioning
confidence: 74%
“…Children with PAE often have arithmetic processing difficulties (Riley and McGee, ), and previous studies have shown altered activity during calculation tasks in the precuneus, right insula, right MFG, and POCG in children and adults with PAE (Meintjes et al, ; Santhanam, Li, Hu, Lynch, & Coles, ; Santhanam et al, ; Woods, Meintjes, Molteno, Jacobson, & Jacobson, ), all regions observed here to have altered connectivity with the sensorimotor regions. The ACC showed higher FC to the right hand sensorimotor region in PAE, also shows higher activation during inhibition tasks (O'Brien et al, ), and altered structure in children and adolescents with PAE compared to controls (Bjorkquist, Fryer, Reiss, Mattson, & Riley, ; Migliorini et al, ). The insula and STG are involved in speech production and language performance (Behroozmand et al, ; Oh, Duerden, & Pang, ), which are known to be impaired in children with FASD (McGee, Bjorkquist, Riley, & Mattson, ; Wyper and Rasmussen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical structure was examined with both thickness and surface area, as these variables follow distinct developmental trajectories (Wierenga et al, 2014). This approach also prevented potential signal dilution errors that occur in measuring their product (volume) (Migliorini et al, 2015). Furthermore, recent work from our laboratory suggests that surface area is a sensitive index to the teratogenicity of prenatal alcohol exposure (Gross et al, 2016).…”
Section: Methodsmentioning
confidence: 99%